Review of unmanned aerial vehicle photogrammetry for aerial mapping applications - Zahari N.M.; Karim M.A.A.; Nurhikmah F.; Aziz N.A.; Zawawi M.H.; Mohamad D. (Springer Science and Business Media Deutschland GmbH, 2023)
3D modeling; Antennas; Data acquisition; Mapping; Offshore oil well production; Open source software; Open systems; Photogrammetry; Three dimensional computer graphics; Topography; Unmanned aerial vehicles (UAV); 3-dimensional; Commercial software; Complex shapes; Low costs; Manned aircraft; Mapping applications; Open source tools; Short periods; Aerial photography